Modelo explicativo do preconceito contra pessoas gordas - Menezes, Thaís de Sousa Bezerra de (2022)
The excess weight (which includes overweight and obesity), despite being a phenomenon that involves social aspects, is mostly investigated by individual aspects. This thesis aimed to propose and validate an explanatory model of prejudice against fat people based on the Attribution of control over the onset weight gain, Attribution of overweight instability, Blame beliefs and Stereotypes about fat people. Thus, the thesis was structured in one theoretical chapter, five studies and final considerations. The first chapter of the thesis is a theoretical chapter whose purpose is to introduce constructs of interest to the work in addition to tracing a historical course on the theme of prejudice against fat people. The first study was presented in article format and aimed to identify beliefs and stereotypes related to prejudice against fat people through a systematic review of the literature. The second study, also presented in article format, was exploratory in nature and aimed to analyze the beliefs identified as relevant to the explanation of prejudice against fat people according to the first study (Attribution of control over the onset weight gain, Attribution of overweight instability, Blame beliefs and Stereotypes about fat people). The sample was 200 individuals from the general population residing in Paraíba. Open questions were used and analyzed through Content Analysis. Closed questions were also included and analyzed with descriptive statistics in SPSS, for the apprehension of beliefs. Free Association (FA) was also used, with the inducing stimulus “fat person”, to obtain stereotypes about fat people. The results indicated the need to assess these beliefs together, investigating their interactions in explaining prejudice against fat people. The third study, in chapter format, presented cross-cultural adaptation studies and exploratory factor analyses of the scales Controllability Scale-Revised (Parry, 2011); Implicit Theories of Weight Management (Burnette, 2010); Competence and Warmth of the Stereotype Content Model by Fiske et al. (2002); Paternalistic Anti-Fat Attitudes Scale (Parry, 2011) and the Measure of Fat Bias (UMB-FAT) (Latner et al., 2008). This study included 200 participants from the general population of Brazilian residents for the exploratory factor analysis, performed using the FACTOR software. The results indicated satisfactory psychometric properties. Furthermore, all cross-cultural adaptations had factor structures similar to those of the original studies. The exception was the UMB-FAT which presented 3 factors instead of the 4 in the original study. Despite this, the UMB-FAT items were grouped in a theoretically and qualitatively coherent way, in addition to having adequate psychometric indices. and 194 participants from the general population of Brazilian residents for the confirmatory factor analysis, performed using the JASP software. The fourth study, also in chapter format, presents the confirmatory analyzes of the scales that were cross-culturally adapted in study III. The study included 194 participants from the general population of Brazilian residents and the analyzes were performed using the JASP software. The psychometric indices proved to be adequate for the factors defined by the exploratory analyzes in study III. Thus, this study indicated that these instruments are suitable for measuring, respectively: Attribution of control over the onset weight gain, through the cross-cultural adaptation of the Controllability Scale-Revised, Attribution of overweight instability through the cross-cultural adaptation of the Implicit scale Theories of Weight Management; Stereotypes about fat people through the cross-cultural adaptation of the Competence and Warmth scales of the Stereotype Content Model, Benevolent prejudice through the cross-cultural adaptation of the Paternalistic Anti-Fat Attitudes Scale and Hostile prejudice against people through the cross-cultural adaptation of the Measure of Fat Bias scale, in future studies. The fifth study, presented in article format, use the instruments previously validated and the blaming instrument against fat people validated by Obara and Alvarenga (2018) to test an explanatory model of prejudice against fat people. The model was built in the Mplus 8 software. It is hoped that this work stimulate future studies and interventions that present accurate information about excess weight that can reduce prejudice towards fat people.